Alpha-particle production in the 6He+120Sn collision. (December 2020) - Lichtenthäler, R.; Appannababu, S.; Alvarez, M. A. G.; Rodríguez-Gallardo, M.; Lépine-Szily, A.; Pires, K.C.C.; Santos, O.C.B.; Umbelino, U.; de Faria, P.N.; Guimarães, V.; Zevallos, E.O.N.; Scarduelli, V.; et al.
Abstract: Alpha particle energy distributions in the 6 He+ 120 Sn collision have been measured at 7 bombarding energies above the Coulomb barrier. A phenomenological analysis of the centroids of the experimental distributions was performed and compared with the expected alpha-particle energies from breakup and neutron transfer reactions. Q-optimum conditions were determined using the Brinks formula for the di-neutron transfer reaction. A comparison of the measured alpha-particle production cross-sections with Continuum Discretized Coupled Channels (CDCC) calculations for breakup is presented.